(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
Prime focus of this article is to check if there are suitable diversification opportunities investing in India. Granger causality tests, vector auto regression (VAR) and dynamic conditional correlation (DCC)–MGARCH are applied to investigate the level of integration between India and Sri Lankan economies. No causality is observed. Outcome of VAR suggest that Sri Lankan economy does not impact the return of the Indian stock market. Applying DCC–MGARCH, it is observed that there is no volatility spillover from Sri Lanka to India in short-run but there is long run spill over of volatility from Sri Lanka to India. The outcomes of the study may assist market managers in setting policies by considering the pattern of volatility transmission from Sri Lankan stock market to Indian stock market.